2021
DOI: 10.3390/ijms22137033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Neural Mechanism of Dysphagia Due to Cancer

Abstract: Cancer is one of the most common causes of death worldwide. Along with the advances in diagnostic technology achieved through industry–academia partnerships, the survival rate of cancer patients has improved dramatically through treatments that include surgery, radiation therapy, and pharmacotherapy. This has increased the population of cancer “survivors” and made cancer survivorship an important part of life for patients. The senses of taste and smell during swallowing and cachexia play important roles in dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…It is listed under code MD93 in the International Classification of Diseases (ICD), 11th revision [2]. OD is a common comorbidity among various patient [3][4][5]. Researchers demonstrated that the prevalence of diagnosed OD was 3% in all adult patients admitted to hospitals in the United States [6] and that it was higher in the population over 75 years old than other age groups [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is listed under code MD93 in the International Classification of Diseases (ICD), 11th revision [2]. OD is a common comorbidity among various patient [3][4][5]. Researchers demonstrated that the prevalence of diagnosed OD was 3% in all adult patients admitted to hospitals in the United States [6] and that it was higher in the population over 75 years old than other age groups [7].…”
Section: Introductionmentioning
confidence: 99%
“…factors of the disease, a considerable number of patients chronically suffer from this condition 6 . Moreover, taste disorder occurring after radiation therapy for cancer of the head and neck and after systemic chemotherapy for other malignancies can be highly refractory to treatment 7 .…”
Section: Introductionmentioning
confidence: 99%
“…factors of the disease, a considerable number of patients chronically suffer from this condition 6 . Moreover, taste disorder occurring after radiation therapy for cancer of the head and neck and after systemic chemotherapy for other malignancies can be highly refractory to treatment 7 .…”
Section: Introductionmentioning
confidence: 99%